Snake Dreams : Charlie Moon #13 - Doss, James D. (New York : St. Martin's Minotaur, 2008)
Ute rancher and part-time tribal investigator Charlie Moon's plans for marital bliss with FBI Special Agent Lila Mae McTeague are put on hold thanks to Charlie's cantankerous aunt, her sixteen-year-old niece, and their visions of a brutally murdered woman.
Keywords: Moon, Charlie (Fictitious character : Doss) -- Fiction; Police -- Colorado -- Fiction; Ute Indians -- Fiction; Colorado -- Fiction; Mystery fiction